Maddison Funk: capstone - Funk, Maddison, artist (Colorado State University. Libraries, 2016)
The artist's statement: My time at CSU has been well spent, honing design, video, and interactive media skills, learning lessons in flexibility, design process, the significance of deadlines, working within a team, strengthening visual, verbal, written communication skills, working with multiple applications/programs as well as understanding the relevance and impact of creativity and resourcefulness. My work exemplifies a variety of these skills that I have learned in my 4 years here at CSU, including animation, video, logo/branding design, poster design, and environmental art. I am extremely proud of these pieces and look forward to creating more in the future.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design